2017
DOI: 10.18632/oncotarget.22435
|View full text |Cite
|
Sign up to set email alerts
|

Neurocan, an extracellular chondroitin sulfate proteoglycan, stimulates neuroblastoma cells to promote malignant phenotypes

Abstract: Neurocan (NCAN), a secreted chondroitin sulfate proteoglycan, is one of the major inhibitory molecules for axon regeneration in nervous injury. However, its role in cancer is not clear. Here we observed that high NCAN expression was closely associated with the unfavorable outcome of neuroblastoma (NB). NCAN was also highly and ubiquitously expressed in the early lesions and terminal tumor of TH-MYCN mice, a NB model. Interestingly, exogenous NCAN (i.e., overexpression, recombinant protein and conditioned mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…As mentioned previously, HSPGs promote the differentiation of neuroblasts, while surface expression of HSPGs and release of soluble forms from the stroma promote FGF2 signaling, which suppresses proliferation in neuroblastoma . Recently, it was reported that NCAN is highly expressed in neuroblastoma and induces an undifferentiated status and stimulates cell division, thereby promoting the malignancy of neuroblastoma cells by providing a growth advantage .…”
Section: Brain Pathogenesismentioning
confidence: 85%
“…As mentioned previously, HSPGs promote the differentiation of neuroblasts, while surface expression of HSPGs and release of soluble forms from the stroma promote FGF2 signaling, which suppresses proliferation in neuroblastoma . Recently, it was reported that NCAN is highly expressed in neuroblastoma and induces an undifferentiated status and stimulates cell division, thereby promoting the malignancy of neuroblastoma cells by providing a growth advantage .…”
Section: Brain Pathogenesismentioning
confidence: 85%
“…In response to hypoxia, high glucose, and inflammation conditions, multiple signaling pathways are activated in these cells, which are involved in retinal remodeling following retinal damage [ 24 ]. Furthermore, high NCAN expression has been associated with unfavorable outcome in neuroblastoma, as it induces an undifferentiated phenotype that promotes the malignancy [ 25 ]. ATP6V1C1 belongs to the vacuolar (H+)-ATPases (or V-ATPases) family that is responsible for the acidification of intracellular compartments in eukaryotic cells [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the four genes, AHCY has been reported to be a direct target of MYCN , which predicts poor prognosis in NB ( Chayka et al, 2015 ). NCAN has been confirmed to promote the malignant phenotypes in NB cells ( Su et al, 2017 ). ERCC Excision Repair 6 Like ( ERCC6L , Spindle Assembly Checkpoint Helicase) is a protein-coding gene, also known as PICH, its related pathways include cell cycle and mitosis.…”
Section: Discussionmentioning
confidence: 99%